TINDAK PIDANA KORUPSI PROYEK EMBUNG MNELALETE KECAMATAN AMANUBAN BARAT KABUPATEN TIMOR TENGAH SELATAN PROVINSI NUSA TENGGARA - Oematan, Syarah Dyana; Fallo, Debi. F. Ng; Manuain, Orpa G. (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
Corruption is an irresponsible act that causes harm to the nation, the state, and society. The rampant occurrence of corruption in Indonesia is caused by various factors, one of which is the gap between the laws and regulations and the practices that occur in court. This gap ultimately makes perpetrators feel relatively safe when committing acts of corruption. In the case of Jemmy Unbanunaek, there was a discrepancy between the laws and the judge’s decision, as Jemmy was not a civil servant but was charged under Article 3 of the Corruption Eradication Act (UUTPK), which applies to civil servants. This indicates that the judge did not properly consider the legal status of the perpetrator. The type of research used in this study is normative juridical legal research. Normative juridical legal research is conducted using a document study approach, which involves the analysis of documents such as literature data, statutory regulations, court decisions, legal theories, and expert opinions. The technique for collecting legal materials in this research is through literature study. The research findings indicate that: (1) The judge’s legal basis in deciding the corruption case of the Mnelalete reservoir project in South Central Timor Regency was Article 3 of the Corruption Eradication Act (UUTPK). The findings show that the judge applied Article 3 of the UUTPK to prosecute Jemmy Unbanunaek. However, this application was inappropriate because Jemmy did not meet the element of official authority required by Article 3, and he was not a civil servant. (2) The verdict rendered by the judge against Jemmy was legally flawed (error in juris) and mistaken with regard to the subject of the offense (error in persona), and it contradicted the principles of criminal liability and the principle of legality. The judge should have applied Article 2 of the UUTPK, which is more appropriate given Jemmy's status and the unlawful nature of his actions.